HUBUNGAN ANTARA KREATIVITAS GURU DALAM MENGGUNAKAN FASILITAS DAN PERLENGKAPAN OLAHRAGA DENGAN MINAT SISWA PADA PEMBELAJARANPENDIDIKAN JASMANI:Studi Deskriptif Kuantitatif Kompetensi Guru dalam Mengelola Fasilitas dan Perlengkapan Olahraga berdasar Kesan Subyektif Siswa di SMA Negeri Kecamatan Ciamis - Tina Rizka Nuraprilian, - (2012)
The sports facilities and equipment owned by each school varied, creativity is required in the management of a competent teacher, giving rise to interest students in learning physical education. Problem posed is the extent of the relationship between teachers' creativity in using the facilities and sports equipment with interest students in the learning of physical education in Ciamis District Senior High School students based on a subjective impression? The purpose of study to know the description of the relationship between the creativity of teachers in the use of sports facilities and equipment with an interest in teaching students in senior high school physical education based on the Ciamis District subjective impression of the students. The method used is descriptive quantitative approach. The population in this study were high school students Ciamis District. The sample in this study is a class XI student. The research instrument used was questionnaire or questionnaires, observation, interviews and documentation studies. The data obtained were processed according to several aspects, namely: the processing of questionnaires with analysis of the validity and reliability, to measure the relationship between two variables by using the formula coefficient of determination and correlation and regression analysis. The results of data processing and analysis of teachers' creativity in using the facilities and sports equipment and student interest in learning physical education in Ciamis District High School Students Based on Subjective Impression of 0.536. The calculated value of 5.883 with 88 respondents and the alpha value of 5% is obtained t-table value 1.988. Concluded that there is a significant relationship between teachers' creativity in using the facilities and sports equipment to the students' interest in participating in the learning of students in high school students' subjective impressions based Ciamis.